2012
DOI: 10.1111/ctr.12022
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term efficacy of nucleos(t)ide analog plus a year of low‐dose HBIG to prevent HBV recurrence post‐liver transplantation

Abstract: Hepatitis B immunoglobulin (HBIG), given in combination with nucleos(t)ide therapy, has reduced the rate of recurrent hepatitis B virus (HBV) following liver transplantation (LT), although the most effective protocol is unknown. We have retrospectively evaluated the use of long-term nucleos(t)ide analog in combination with one yr of low-dose HBIG. One hundred and fifty-two adults with HBV-related liver disease underwent LT in our center from January 1999 to August 2009; of these, 132 patients who received one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
2
15
1
Order By: Relevance
“…Compared to NA monotherapy, NA treatment in conjunction with HBIG has even better outcomes for HBsAg clearance rates in liver transplantation patients [72,73]. A short course of low-dose HBIG combined with long-term NA antiviral treatment has been demonstrated to be an effective therapy to prevent HBV recurrence in liver transplantation patients [74].…”
Section: Antiviral Treatment Medicationsmentioning
confidence: 99%
“…Compared to NA monotherapy, NA treatment in conjunction with HBIG has even better outcomes for HBsAg clearance rates in liver transplantation patients [72,73]. A short course of low-dose HBIG combined with long-term NA antiviral treatment has been demonstrated to be an effective therapy to prevent HBV recurrence in liver transplantation patients [74].…”
Section: Antiviral Treatment Medicationsmentioning
confidence: 99%
“…Resistance to lamivudine, because of the development of the tyrosine methionine aspartate aspartate (YMDD) mutations, is treated with adefovir, high-dose entecavir or, more recently, tenofovir. Studies have shown that just 1 yr of HBIG when combined with lamivudine, is effective and cost-saving, with only 8.9% of patients developing resistance at 5-10 yr of follow-up (Tanaka et al 2012). All recurrences were treated successfully with additional antiviral therapy.…”
Section: Patients Receiving Transplantationmentioning
confidence: 99%
“…In total, 17 patients died during follow-up with six deaths due to HCC recurrence; however, none of the deceased patients had HBV recurrence. Patient survival rate was noted to be 93.9, 86.9 and 84.1% at years 1, 5 and 10, respectively [15]. Newer nucleos(t)ide analogs such as ETV and TDF have a much higher barrier to resistance rate compared to LAM monotherapy and are, therefore, the preferred therapy, especially in the post-LT setting [9,10].…”
Section: Methodsmentioning
confidence: 99%